Prevalence of endometrial cancer symptoms among overweight and obese women presenting to a multidisciplinary weight management center - Anna L. Beavis; Omar Najjar; Lawrence J. Cheskin; Rohan Mangal; Anne F. Rositch; Geri Langham; Amanda N. Fader (Gynecologic Oncology Reports, 2020)
Endometrial cancer rates are rising in parallel with the obesity epidemic. We aimed to determine the prevalence of endometrial hyperplasia or cancer (EH/EC) bleeding symptoms among at-risk women. We conducted a retrospective cohort study of overweight and obese women at a multidisciplinary weight management center who had completed a gynecologic/menstrual history questionnaire from May 2018 to October 2019. The primary outcome of any EH/EC symptom was defined as follows: in premenopausal women, any recent abnormal uterine bleeding (AUB); in postmenopausal women: any bleeding/discharge. The prevalence of EH/EC symptoms was compared by menopausal status using Fisher’s exact tests, and multivariable regression identified independent factors associated with having EH/EC symptoms. A total of 103 women were included, and 4 (4%) had a history of EH/EC. Of the 84 (n = 82%) of women with no prior hysterectomy, 57% (n = 33/58) of premenopausal women reported any EH/EC symptom compared to 15% (n = 15/26) of postmenopausal women (p < 0.001). Two-thirds of symptomatic premenopausal women had two or more symptoms, most commonly heavy menses (49% (n = 25/51)) and irregular periods (39% (n = 17/44)). Sixty percent (n = 20/33) had discussed these with a gynecologist, and one third had undergone an endometrial biopsy. A history of polycystic ovarian syndrome (RR:1.72, 95% CI 1.24–2.38) was associated with EH/EC symptoms, while being postmenopausal was not (RR:0.32, 95%CI: 0.12–0.87). We demonstrate that EH/EC bleeding symptoms are prevalent in this at-risk population, but frequently are not discussed with gynecologists. Providers who care for obese women should ask about EH/EC symptoms, and provide prompt referrals to facilitate prevention and early detection of this cancer.